Gender Identity & Harassment: Understanding Transgender Harassment Experiences In the Punjab - Dr. Maliha Gull Tarar,; Rana Imran Ahmed,; Dr. Aaqib Shahzad Alvi,; Azeem Fatima, (Al-Qanṭara, 2024)
This paper examines the problem of transgender harassment and the mechanisms underlying such violence. Despite the efforts of advocates for transgender rights both online and offline harassment continues to be a real issue. Transgender people face widespread harassment, including being denied employment, evicted from their homes, insulted in the streets, and even assaulted by police. This paper looks at harassment from various perspectives, including gender identity, socioeconomic status, and culture, as they affect the transgender community. The research aims and objectives are as follows: In the first place, the research seeks to identify and describe various forms of harassment with the goal of providing distinct profiles of the phenomenon. Second, it investigates the causes, with a focus on factors that increase vulnerability to harassment, and explains the roles of social, cultural, and economic backgrounds. Furthermore, the current study evaluates the efficacy of existing support measures, such as legislation, support groups, and awareness creation, in addressing harassment and providing support to transgender persons. The paper concludes with evidence-based practice recommendations for policymakers, activists, and community agencies to improve prevention factors, supportive structures, and legal protection for transgender people and other marginalized groups in an attempt to make this society a better place for each unique individual. As a result, this study contributes to the discussion about transgender people’s rights by providing information on the dynamics of harassment.